High efficiency low power RF energy harvesting system for LTE band and IoT applications - Taha, Bilal Salman; Rhazali, Zeti Akma; Sampe, Jahariah; Abdul Malek, Norun Farihah; Zeain, Mohammed Yousif; Alkaseh, Adel M. (Electromagnetic Academy (USA), 2025)
The prospective applications of a rectangular microstrip patch antenna (MPA) in energy harvesting at radio frequencies (EH). The study aims to develop a rectenna that can detect and connect low power wireless devices to long-term evolution (LTE) networks by capturing low-power radio frequency (RF) signals radiated by cell towers, since the Kappa 438 antenna substrate with relative permittivity 4.25 has high 9 dB gain and 83% of measured efficiency. For the 2.5 GHz LTE band, stubs technology is being used for impedance matching and to decrease the overall rectenna size. The captured RF signals were altered into a usable DC voltage via a rectifier circuit in the manufactured rectenna, having the option of storing the voltage in a battery or utilizing it to power wearable, portable Internet of Things (IoT) systems and wireless sensors. The rectifier circuit is reduced in size by utilizing the SMD-Schottky diode type SMS7630 segments approach, further reducing the complexity and bulk of the rectenna. The rectenna obtains an efficiency of 88% when the RF input power is tuned to 0 dBm, while the maximum output DC voltage generated is 1.7 V when the radio waves power supply is 10 dBm. The rectenna with high gain and directivity has the capability to operate in low power environments, capturing weak radio frequency signals and working across -10 to 10 dBm power dynamic range. power dynamic range. These outcomes represent new contribution to our work which is relevant to other studies listed in Table 6 and demonstrated notable improvements.